Dynamic auxin transport patterns preceding vein formation revealed by live-imaging of Arabidopsis leaf primordia - Marcos, Danielle; Berleth, Thomas (Frontiers in Plant Science, 2014)
Self-regulatory patterning mechanisms capable of generating biologically meaningful, yet unpredictable cellular patterns offer unique opportunities for obtaining mathematical descriptions of underlying patterning systems properties. The networks of higher-order veins in leaf primordia constitute such a self-regulatory system. During the formation of higher-order veins, vascular precursors are selected from a homogenous field of subepidermal cells in unpredictable positions to eventually connect in complex cellular networks. Auxin transport routes have been implicated in this selection process, but understanding of their role in vascular patterning has been limited by our inability to monitor early auxin transport dynamics in vivo. Here we describe a live-imaging system in emerging Arabidopsis thaliana leaves that uses a PIN1:GFP reporter to visualize auxin transport routes and an Athb8:YFP reporter as a marker for vascular commitment. Live-imaging revealed common features initiating the formation of all higher-order veins. The formation of broad PIN1 expression domains is followed by their restriction, leading to sustained, elevated PIN1 expression in incipient procambial cells files, which then express Athb8. Higher-order PIN1 expression domains (hPEDs) are initiated as freely ending domains that extend toward each other and sometimes fuse with them, creating connected domains. During the restriction and specification phase, cells in wider hPEDs are partitioned into vascular and non-vascular fates: Central cells acquire a coordinated cell axis and express elevated PIN1 levels as well as the pre-procambial marker Athb8, while edge cells downregulate PIN1 and remain isodiametric. The dynamic nature of the early selection process is underscored by the instability of early hPEDs, which can result in dramatic changes in vascular network architecture prior to Athb8 expression, which is correlated with the promotion onto vascular cell fate.